PENGARUH GENDER, KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR, DAN KOMPETENSI PROFESIONAL TERHADAP AUDIT JUDGEMENT - Ika Sulistyawati, Ardiani; Santoso, Aprih; Prastiti, Dina Sita (FEB Universitas Sam Ratulangi Manado, 2019)
This study aims to examine and analyze the effects of Gender, Complexity of Duties, Experience Auditors, and Professional Competence of Judgment Audit. This research uses a sample of auditors who work at Public Accounting Firm in Central Java and DIY Provinces. This experience was carried out using a questionnaire at Public Accounting Firm in Central Java and Yogyakarta with 89 respondents. Of the 121 questionnaires distributed, only 89 questionnaires could be used. Data analysis techniques in this study using multiple linear regression analysis, Test Validity and Realibility Test. In addition all variables have been tested using Classic Assumption Test.Based on t test by using multiple regression model indicate that task complexity, auditor experience and professional competence have an effect on audit judgment, while gender does not affect to audit judgment